Mind-reading difficulties in the siblings of people with Asperger's syndrome: evidence for a genetic influence in the abnormal development of a specific cognitive domain. - Dorris, L; Espie, C; Knott, F; Salt, J (2004)
BACKGROUND: Previous research suggests that the phenotype associated with Asperger's syndrome (AS) includes difficulties in understanding the mental states of others, leading to difficulties in social communication and social relationships. It has also been suggested that the first-degree relatives of those with AS can demonstrate similar difficulties, albeit to a lesser extent. This study examined 'theory of mind' (ToM) abilities in the siblings of children with AS relative to a matched control group. METHOD: 27 children who had a sibling with AS were administered the children's version of the 'Eyes Test' (Baron-Cohen, Wheelwright, Stone, and Rutherford, 1999). The control group consisted of 27 children matched for age, sex, and a measure of verbal comprehension, and who did not have a family history of AS/autism. RESULTS: A significant difference was found between the groups on the Eyes Test, the 'siblings' group showing a poorer performance on this measure of social cognition. The difference was more pronounced among female siblings. DISCUSSION: These results are discussed in terms of the familial distribution of a neuro-cognitive profile associated with AS, which confers varying degrees of social handicap amongst first-degree relatives. The implication of this finding with regard to the autism/AS phenotype is explored, with some discussion of why this neuro-cognitive profile (in combination with corresponding strengths) may have an evolutionary imperative.